Żywotność formy językowej Witolda Gombrowicza w literaturze ostatnich dekad - Sławkowa, Ewa (Stylistyka, 2020)
Starting with the thesis that Gombrowicz’s unique “linguistic form”, which is a stylistic equivalent of form as an anthropological-philosophical category, we claim that it has become an important point of reference, a kind of stylistic stamp or matrix, used and modified by contemporary Polish authors. Following Olaf Kühl’s suggestions in his Stilistik einer Verdrängung. Zur Prosa von Witold Gombrowicz, we assume that indeterminacy and ambiguity are most characteristic features of Gombrowicz’s style clearly manifested upon the level of semantics (polysemy) and syntax (nominalised construction, retardation syntax). Reading texts by Wojciech Kuczok, Jerzy Pilch, Micha³ Witkowski, and Szczepan Twardoch, we find variously functionalized features of this style on all formal and thematic levels.